A Numerical Study on Mechanical Seal Dynamic Characteristics Within a Reactor Coolant Pump - Wang, Jun-Li; Chen, Xing-Yuan; Binama, Maxime; Su, Wen-Tao; Wu, Jian (Frontiers in Energy Research, 2022)
The dynamic characteristics of the reactor coolant pump’s mechanical seal are very important for the safe operation of the reactor coolant pump. In this paper, based on the moving grid technology, a 3D fluid-structure interaction analysis model is established. The influence of inlet pressure fluctuation, closing force fluctuation and speed fluctuation on mechanical seal characteristics within a reactor coolant pump is numerically studied. The results show that when pressure and closing force fluctuations are applied, the static ring displacement, inlet-to-outlet temperature difference as well as the leakage difference show similar variation rules. In addition, it is found that the sealing parameters are more sensitive to the step form of fluctuation. When the step change of 4% closing force is applied, the static ring displacement is more than 36.7%, the change of the temperature difference between inlet and outlet zones exceeds 53.5%, and the leakage difference is more than 127.2%. The change of speed is also found to significantly affect the temperature difference between the inlet and outlet of the reactor coolant pump’s mechanical seal, but the effect on the leakage and opening force is negligible.